Teacher’s Strategies In Teaching English Vocabulary at SMPN 1 Tanjungpinang - Dinda Widianda; Fauzan Abdul Hakim; Rizky Aditya; Fitri Noviyanti; Erwin Pohan (CV. Kalimasada Group Profesional, 2024)
The purpose of this study is to outline the methods that educators employ when instructingstudents in language. Qualitative descriptive research examines information gathered fromEnglish teachers' interviews. Considering the outcomes, inferences regarding the teacher'stactics have been drawn from the interviews. The instructors that are employed include: (1)Game Use: Teachers play games like